2023
DOI: 10.1002/prot.26510
|View full text |Cite
|
Sign up to set email alerts
|

The structural analysis of the periplasmic domain of Sinorhizobium meliloti chemoreceptor McpZ reveals a novel fold and suggests a complex mechanism of transmembrane signaling

Abstract: Chemotaxis is a fundamental process whereby bacteria seek out nutrient sources and avoid harmful chemicals. For the symbiotic soil bacterium Sinorhizobium meliloti, the chemotaxis system also plays an essential role in the interaction with its legume host. The chemotactic signaling cascade is initiated through interactions of an attractant or repellent compound with chemoreceptors or methyl‐accepting chemotaxis proteins (MCPs). S. meliloti possesses eight chemoreceptors to mediate chemotaxis. Six of these rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The number of MCPs per rhizobial genome varies greatly, with less than 10 in Sinorhizobium and Ensifer spp. to over 30 in R. leguminosarum or Bradyrhizobium japonicum isolates (Scharf et al, 2016), although only a few of them have assigned functions (Compton & Scharf, 2021; Salar et al, 2023). Genome analysis revealed that Rlv3841 has 27 predicted chemoreceptors, with a wide variety of sensory domains and phylogenetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The number of MCPs per rhizobial genome varies greatly, with less than 10 in Sinorhizobium and Ensifer spp. to over 30 in R. leguminosarum or Bradyrhizobium japonicum isolates (Scharf et al, 2016), although only a few of them have assigned functions (Compton & Scharf, 2021; Salar et al, 2023). Genome analysis revealed that Rlv3841 has 27 predicted chemoreceptors, with a wide variety of sensory domains and phylogenetic diversity.…”
Section: Discussionmentioning
confidence: 99%

Bacterial sensor evolved by decreasing complexity

Monteagudo-Cascales,
Gavira,
Xing
et al. 2024
Preprint
Self Cite